Accessing low-oxidation state taxanes: is taxadiene-4(5)-epoxide on the taxol biosynthetic pathway?. Issue 5 (4th February 2016) - Barton, Naomi A.; Marsh, Benjamin J.; Lewis, William; Narraidoo, Nathalie; Seymour, Graham B.; Fray, Rupert; Hayes, Christopher J.
Abstract : We report the first synthesis of taxadiene-4(5)-epoxide, which rearranges upon acid treatment to produce products of relevance to taxol biosynthesis. Abstract : We have shown for the first time that taxadiene (3 ) can be epoxidised in a regio- and diastereoselective manner to provide taxadiene-4(5)-epoxide (12 ) as a single diastereoisomer, and that this epoxide can be rearranged to give taxa-4(20), 11(12)-dien-5α-ol (4 ). Furthermore, the epoxide12 rearranges under acidic conditions to give taxa-4(20), 11(12)-dien-5α-ol (4 ), the known bridged ether OCT (5 ) and the new oxacyclotaxane (OCT2)15 . Contrary to previous speculation, taxadiene-4(5)-epoxide (12 ) is susceptible to rearrangement when exposed to an iron III porphyrin, and these observations justify consideration of epoxide12 as a chemically competent intermediate on the taxol biosynthetic pathway.